2020
DOI: 10.13189/ujer.2020.082565
|View full text |Cite
|
Sign up to set email alerts
|

Exploring University Students' Preferences towards Written Corrective Feedback in EFL Context in Libya

Abstract: This study was designed to explore Libyan EFL students' written corrective feedback preferences regarding their gender to explore the relationship between their gender and their preferences. The data were collected by applying a quantitative method by using a questionnaire. The main objective of this study was to investigate students' preferences on six types of Written Corrective Feedback and investigate which of these types they preferred the most. The researcher administered the questionnaire to a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(39 reference statements)
2
0
0
Order By: Relevance
“…We explored that learners also like when their teacher corrects all their errors; they expect unfocused feedback on their writing. The findings correspond with the research of (Radecki& Swales, 1988;Enginarlar, 1993;Jahbel, Latief, Cahyono, & Abdalla, 2020). The findings of this study showed that learners favored the unfocused feedback i.e., they like when all the errors corrected, for unfocused feedback contributes to learning.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We explored that learners also like when their teacher corrects all their errors; they expect unfocused feedback on their writing. The findings correspond with the research of (Radecki& Swales, 1988;Enginarlar, 1993;Jahbel, Latief, Cahyono, & Abdalla, 2020). The findings of this study showed that learners favored the unfocused feedback i.e., they like when all the errors corrected, for unfocused feedback contributes to learning.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study showed that learners favored the unfocused feedback i.e., they like when all the errors corrected, for unfocused feedback contributes to learning. This finding is similar to (Leki, 1991;Cohen, 1987;Cumming, 1995;Ferris, 1995;Hyland, 1998;Lee, 2004;Jahbel, et al,2020). There is no correlation in this study between teachers' and learners' preferences regarding written feedback types.…”
Section: Discussionsupporting
confidence: 86%